1999
DOI: 10.1021/ma9801016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Anionic Cyclopolymerization of Bis(dimethylvinylsilyl)methane

Abstract: The driving force of the complete cyclization in the anionic cyclopolymerization of bis(dimethylvinylsilyl)methane with n-BuLi/TMEDA in hexane is clarified with resonance Raman and 1H NMR measurements. Vinyl groups coordinating to the lithium cation are detected in both measurements of the polymerization mixture at −70 °C, and they, at least some part of them, are shown to be the vinyl groups in uncyclized end units. Disappearance of these species from the resonance Raman spectrum at −20 °C indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The IR spectrum of 2 features a CC stretch at 1628 cm –1 that is 13 cm –1 lower than the 1641 cm –1 frequency seen for its conjugate acid 4,4-dimethyl-1-pentene . This observation is consistent with previous infrared and resonance Raman studies of lithium–olefin complexes. ,, However, the lowered CC stretching frequency is not definitive evidence of the presence of a Li–olefin interaction because this mode can be affected by other factors such as coupling to other vibrations, strain, and inductive effects …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The IR spectrum of 2 features a CC stretch at 1628 cm –1 that is 13 cm –1 lower than the 1641 cm –1 frequency seen for its conjugate acid 4,4-dimethyl-1-pentene . This observation is consistent with previous infrared and resonance Raman studies of lithium–olefin complexes. ,, However, the lowered CC stretching frequency is not definitive evidence of the presence of a Li–olefin interaction because this mode can be affected by other factors such as coupling to other vibrations, strain, and inductive effects …”
Section: Resultssupporting
confidence: 91%
“…We briefly consider here the question of the rate-determining step in carbolithiation reactions. , Carbolithiation reactions are thought to proceed through a monomeric (i.e., Lewis-base-coordinated) lithium species in which the anionic carbon and the olefin are simultaneously bound to lithium. , Although ab initio studies of gas phase carbolithiation reactions have suggested that coordination of the olefin to lithium is downhill thermodynamically by 12 kcal/mol, , these calculations involved unsolvated organolithium monomers, which are quite different from the species actually present in solution. Our studies suggest that, in THF, which is a common solvent for carbolithiation reactions, the dominant species in solution before carbolithiation occurs are ones in which no Li–olefin interactions are present.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations